o‘spirinlik yosh davrida tafakkur jarayoniga ta’sir etuvchi psixologik omillar - Djolimbetova, M.M. (SCIENCE and SOCIETY, 2024)
The article are analyzed psychological factors influencing the development of mental processes in adolescence. Mainly, the factors are analyzed influencing the processes and definitions in the old classes of children's general education schools, academic lyceums, vocational colleges and higher educational institutions in pre-adolescence.
Keywords: problem psychological cognition; development cognition; development conscious ness; thinking; comparison; analysis and decision mahing